High Asymptomatic Carriage of Carbapenem-resistant Enterobactiaceae and Vancomycin-resistant Enterococcus by Active Screening for Intubated Patients in Intensive Care Units and Respiratory Care Units. (4th October 2017) - Lee, Yu-Lin; Hou, I-Lun; Lai, Tzu-Yin; Chang, Hui-Lan; Lai, Huei-Wen; Liu, Chun-Eng; Lin, Szu-Han
Abstract: Background: Multi-drug-resistant organisms (MDROs) pose a threat to human health in recent years. Asymptomatic colonization of MDROs was often overlooked and played an underestimated role in nosocomial infection. Methods: From September 2015 to December 2016, a prospective study was conducted in Changhua Christian hospital, a tertiary hospital with 1, 684 inpatient beds. Rectal swabs were collected for every intubated patient admitted to our intensive care units (ICU) and respiratory care units (RCU). A selective culture medium (ChromID™ CARBA agar) was used for active screening of carbapenem-resistant Escherichia coli (CREC), carbapenem-resistant Klebsiella pneumoniae (CRKP) and vancomycin-resistant enterococci (VRE). A multivariate logistic regression model was applied to identify independent variables associated with positive stool carriage of MDROs. CRKP was further tested for Klebsiella pneumonia carbapenemase (KPC) and New Delhi metallo-β-lactamase 1 (NDM-1) gene. Pulsed-field gel electrophoresis was used for phylogenetic analysis. Results: A total of 1, 146 patients were screened for asymptomatic carriage of enteral MDROs. The carriage rates by rectal swab were 13.1%, 0.3% and 6.4% for VRE, CR-EC and CR-KP, respectively. The factors associated with positive stool carriage of MDROs including age (relative risk [RR], per 1-year increase, 1.01; 95% confidence interval [CI], 1.00–1.02, P = 0.035), chronic respiratory failure with long-term intubation (RR 3.07; 95% CI, 1.89–5.00, P < 0.001), and recent broad-spectrum antibiotics exposure (RR 2.50; 95% CI, 1.83-3.43, P < 0.001). The 64.5% of CRKP from rectal swab was positive for KPC gene but none was positive for NDM-1 gene. All KPC positive CRKP were belonged to same genotype by PFGE. Conclusion: A high rate of asymptomatic CRE and VRE carriage was demonstrated by active screen for intubated patient admitted to ICU and RCU. The PFGE analysis of CRKP disclosed a single strain transmission in the study hospital. In addition to proactive isolation, study aiming on methods of de-colonization is warranted to prevent further intra-hospital transmission. Disclosures: All authors: No reported disclosures.